Can long‐lived species keep pace with climate change? Evidence of local persistence potential in a widespread conifer. Issue 2 (21st November 2020) - Bisbing, Sarah M.; Urza, Alexandra K.; Buma, Brian J.; Cooper, David J.; Matocq, Marjorie; Angert, Amy L.
Abstract: Aim: Climate change poses significant challenges for tree species, which are slow to adapt and migrate. Insight into genetic and phenotypic variation under current landscape conditions can be used to gauge persistence potential to future conditions and determine conservation priorities, but landscape effects have been minimally tested in trees. Here, we use Pinus contorta, one of the most widely distributed conifers in North America, to evaluate the influence of landscape heterogeneity on genetic structure as well as the magnitude of local adaptation versus phenotypic plasticity in a widespread tree species. Location: Western North America. Methods: We paired landscape genetics with fully reciprocal in situ common gardens to evaluate landscape influence on neutral and adaptive variation across all subspecies of P. contorta . Results: Landscape barriers alone play a minor role in limiting gene flow, creating marginal geographically‐based structure. Local climate determines population performance, with survival highest at home but growth greatest in mild climates (e.g., warm, wet). Survival of two of the three populations tested was consistent with patterns of local adaptation documented for P. contorta, while growth was indicative of plasticity for populations grown under novel conditions and suggesting that some populations are not currently occupying their climatic optimum. Main Conclusions: Our findings provide insight into the role of the landscape in shaping population genetic structure in a widespread tree species as well as the potential response of local populations to novel conditions, knowledge critical to understanding how widely distributed species may respond to climate change. Geographically based genetic structure and reduced survival under water‐limited conditions may make some populations of widespread tree species more vulnerable to local maladaptation and extirpation. However, genetically diverse and phenotypically plastic populations of widespread trees, such as many of the P. contorta populations sampled and tested here, likely possess high persistence potential.